Co-Production and Co-Creation - Ann Starbæk Bager; Lone Hersted; Ottar Ness (Akademisk Kvarter, 2021)
Over the past decade, co-production and co-creation have become central buzzwords throughout society. The terms engender a fundamental participatory ethos, entailing an increasing involvement in decision-making processes of a variety of people across diverse contexts, who should be given a voice in a wide range of practices to a higher degree than previously done. To a large extent, this participatory wave thus creates new challenges and dilemmas for employees in contemporary organizations. For instance, many public employees (frontline workers) experience challenges regarding translating (and/or enacting) co-creative/co-productive policy objectives into (in) their practices. A central obstacle seems to be the fact that existing organizational frameworks and conditions are often rooted in contradictory management paradigms and reified institutionalized practices, complicating participatory aspirations and processes in various ways. In different ways, the contributions in this issue critically address and discuss a variety of challenges related to co-production and co-creation in contemporary society.